Factors influencing inconsistent attendance for outpatient physiotherapy treatment among stroke patients at mansa general hospital - Mambwe, Steward (Lusaka: University of Zambia , School of Medicine)
In rural areas the implementation of good stroke management is compromised especially in developing countries like Zambia. In hese areas, stroke care is often fragmented and does not adhere to recommended guidelines. This is a result of poor accessibility to health services such as poor road network. Adherence is a common and serious problem among stroke patients especially those in rural areas. the objective of this study was to determine factors adversely influencing incossitent attendance for outpatient physiotherapy treatment among stroke patients at mansa general hospital.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Cerebrovascular disease--Patients--Rehabilitation.